Baby dinosaur on the farm follow baby dinosaur on his search for farmyard fun! - Mills, Andrea; Emerson, Emily; Price, Holly (London dorling kindersley, 2022)
STOMP! STOMP! STOMP! Who could that be?! It's Baby Dinosaur and he's finally arrived on the farm. This can only mean one thing - it's time to get your wellies on and join him on his adventures! But when Baby Dinosaur notices that his new farmyard friends could use his help, he springs into action. With a ROAR so loud and a neck so long, Baby Dinosaur is a welcome addition. After all, what is a friend if not someone who will lend a hand when you need it. Follow this spirited dinosaur as he searches for some farmyard fun, and along the way teaches little ones all about lending a helping hand
English Stories
Keywords: English stories